Mythos y logos en Parménides - Fattal, Michel (2009)
Si bien Parménides no otorga, como Jenófanes, una connotación fuertemente negativa al discurso mítico de la tradición poética, no es menos cierto que asistimos con él a una verdadera transmutación del discurso homérico y hesiódico, fundamentalmente en lo que concierne al problema complejo de la verdad, el engaño y la verosimilitud. La originalidad filosófica de Parménides consistiría no solamente en la elaboración de un logos que encarnaría por primera vez en Occidente la idea de una “razón crítica personal”, capaz de “juzgar” la refutación enunciada por la autoridad de una “maestra de la verdad”, y en el establecimiento de un gnōmē (juicio) susceptible de elegir entre lo más verosímil y lo menos verosímil, sino también en el hecho de entablar, mucho antes que Platón –y a diferencia del Sofista–, una reflexión sobre la verdad y el error que está guiada por la cuestión de las buenas y malas mezclas, las buenas y malas separaciones.---“Mythos and logos in Parmenides”. Although Parmenides does not present a strongly negative connotation of the mythical discourse of the poetic tradition, as Xenophanes does, there is no less truth to the fact that we witness with him a true transmutation of the Homeric and Hesiodic discourse, especially regarding the complex problem of truth, deceit and verisimilitude. The philosophical originality of Parmenides lies not only in the elaboration of a logos that would, for the first time in Western Thought, embody the idea of a “personal critical reason”, capable of “judging” the refutation pronounced by the authority of a “Master of Truth”, nor in the institution of a gnōmē (judgement) capable of choosing between things with more or less verisimilitude, but also in the fact of undertaking, long before Plato –and in a different manner than in the Sophist–, a reflection on truth and error that is guided by the question of the good and bad combinations, the good and bad separations.